DIGITAL SOCIAL STUDIES LEARNING WITH LOCAL COFFEE: A COMMUNITY-BASED APPROACH FROM THE FIELD TO THE DIGITAL MARKETPLACE - Amri Dhimas Maulana; Sela Rachmawati; Sukidin; Mohamad Na’im; Nabella Dananier (Titik Fokus Karya, 2025)
This study explores the implementation of digital social studies learning integrated with local coffee potential through a Community-Based Learning (CBL) approach in junior high schools located in coffee-producing areas of Jember Regency. The study is grounded in the challenge of social studies learning that often remains theoretical and disconnected from students’ social realities. Positioned within the discourse of contextual and transformative education, this research examines how local community resources can be integrated with digital technology to enhance learning relevance. Using a qualitative case study design, data were collected through in-depth interviews, participatory observation, and documentation involving teachers, students, school principals, coffee farmers, and local entrepreneurs. The findings indicate that integrating local coffee potential into digital social studies learning increases student engagement, conceptual understanding of socio-economic processes, digital literacy, and entrepreneurial awareness. Students demonstrated higher motivation and creativity through project-based activities such as field observations, interviews, and digital content production. The study concludes that community-based digital social studies learning rooted in local potential offers an effective and replicable model for creating meaningful, contextual, and future-oriented education, particularly in rural and agrarian contexts.